Mapping Digital Archives Research Trends: A Bibliometric Study Using the Dimensions Database (2020–2024) - Sukarman, Sukarman; Harianto, Harianto; Amalia, Nur (Inkunabula: Journal of Library Science and Islamic Information, 2026)
This study aims to analyze research topic trends related to digital archives using a bibliometric approach. The method employed is bibliometric analysis, with data sourced from the Dimensions database using the keyword "digital archives" for the period 2020–2024, resulting in a total of 428 documents. These documents were analyzed by combining the use of VOSviewer and RStudio software. The analysis results show that research on digital archives has experienced dynamic growth, marked by thematic diversification that includes digitalization, cultural preservation, and connections with social media. Temporally, there is a noticeable shift in research focus from conventional issues to more participatory and technology-based approaches. Scientific literature is also concentrated in a small number of core journals, while author contributions are predominantly limited to single publications. These findings underscore the importance of strengthening scholarly collaboration and developing publication strategies to support the maturation of digital archives as an emerging academic discipline. Abstrak Penelitian ini bertujuan untuk menganalisis tren topik penelitian terkait arsip digital melalui pendekatan bibliometrik. Metode yang digunakan adalah analisis bibliometrik dengan sumber data berasal dari database Dimensions, menggunakan kata kunci “arsip digital” untuk periode 2020–2024, dan menghasilkan sebanyak 428 dokumen. Dokumen tersebut dianalisis dengan mengombinasikan perangkat lunak VOSviewer dan RStudio. Hasil analisis menunjukkan bahwa penelitian mengenai arsip digital mengalami pertumbuhan yang dinamis, ditandai oleh diversifikasi tema yang mencakup digitalisasi, pelestarian budaya, serta keterkaitan dengan media sosial. Dari sisi temporal, terlihat pergeseran fokus riset dari isu-isu konvensional ke pendekatan partisipatif dan berbasis teknologi. Literatur ilmiah juga terkonsentrasi pada sejumlah kecil jurnal inti, sedangkan kontribusi penulis didominasi oleh publikasi tunggal. Temuan ini menegaskan pentingnya penguatan kolaborasi ilmiah dan pengembangan strategi publikasi untuk mendukung kematangan bidang arsip digital sebagai disiplin yang berkembang.